Bioactive Guided Fractions of Annona reticulata L. bark: Protection against Liver Toxicity and Inflammation through Inhibiting Oxidative Stress and Proinflammatory Cytokines - Kandimalla, Raghuram; Dash, Suvakanta; Kalita, Sanjeeb; Choudhury, Bhaswati; Malampati, Sandeep; Kalita, Kasturi; Kotoky, Jibon (Frontiers in Pharmacology, 2016)
Herbal medicine is popularized worldwide due to its ability to cure the diseases with lesser or no side effects. North Eastern part of India comes under one of the world biodiversity hotspots which is very rich in traditional herbal medicine. Annona reticulata L. (Annonaceae) is one such plant used for the treatment of inflammatory diseases, liver ailments and diabetes by traditional healers. The present study was aimed to scientifically validate this folk knowledge and to develop an herbal remedy through evaluating bioactive guided fractions of A. reticulata (AR) bark against hepatotoxicity and inflammation using in vitro and in vivo models. Results of this study demonstrates that among all fractions of AR bark, methanol extract and its water fraction possess strong anti-oxidant ability and showed protection against CCl4 induced toxicity in HepG2 cell lines and rats. Both the fractions also exhibit dose dependent anti-inflammatory activity against carrageenan induced inflammation in rats. Water fraction showed potent response in the entire tests conducted than methanol extract, which states that polar components of the AR bark methanol extract were responsible for these activities. Further, from the experiments conducted to elucidate the mechanism of action, the results revealed that AR bark showed liver protection and anti-inflammatory response through inhibiting the oxidative stress and inflammatory cytokines.